Plasmon resonances and their guality factors in a finite linear chain of coupled metal wires - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2013)
This paper presents a straightforward analysis of the plasmonic properties of metal wires arranged in a linear chain of a finite length. For this we solve eigenvalue problem in form of matrix equations that allow thorough investigation of plasmonic modes with different field distributions. Our modeling provides results in terms of eigen oscillating frequencies and quality factors with controllable accuracy. It has revealed the possibility of quality factor dramatic enhancement for certain plasmonic modes by adjusting the separation distances and increasing the number of wires in a chain.
Keywords: Eigenvalues; nanowires; plasmons